Functional enzyme delivery via surface-modified mesoporous silica nanoparticles in 3D printed nanocomposite hydrogels - Mahran, Alaa; Howaili, Fadak; Bhadane, Rajendra; Mathiyalagan, Rathna; Viitala, Tapani; Wang, Xiaoju; Rosenholm, Jessica M. (Elsevier BV, 2025)
Three-dimensional (3D) printed hydrogel-based scaffolds have emerged as promising for the delivery of biologicals. Recently, we developed a printable plant-based nanocomposite hydrogel, composed of anionic cellulose nanofibers (T-CNF) and methacrylated galactoglucomannan (GGMMA), reinforced with mesoporous silica nanoparticles (MSNs) of different surface charges. However, ensuring the biological activity of the delivered biomolecules requires further investigation to validate the functionality of the developed biomaterial. To investigate this, in this study, horseradish peroxidase (HRP) and lysozyme were selected as distinct model proteins, assessing their immobilization stability and biological activity after MSN immobilization and 3D printing. The interactions between the enzymes and differently surface-modified MSNs were explored using multi-parametric surface plasmon resonance (MP-SPR) and molecular dynamics (MD) simulations. We observed that MSN surface charge is key to the extent of enzyme adsorption and activity control. Positively charged MSNs showed the highest HRP immobilization but caused significant activity loss in both enzymes. In contrast, near-neutral and negatively charged MSNs provided improved stability and activity retention for HRP and lysozyme, respectively. Except for lysozyme/hydrogel, HRP/hydrogel and enzyme-loaded nanocomposite hydrogels (HRP-loaded near-neutral and lysozyme-loaded negatively charged MSNs) were successfully 3D printed using different UV post-curing times. While enzyme-laden nanocomposite scaffolds showed promising immobilization stability, the presence of the photoinitiator caused significant inactivation for both enzymes. Irrespective of the crosslinking approach, this matrix demonstrates significant potential as a delivery carrier for various biomolecules, with promising applications in tissue engineering and wound healing.
Keywords: Cellulose nanofibers; Hydrogel extrusion 3D printing; MD simulation; Mesoporous silica nanoparticles; Nanocomposite biomaterial; Protein-nanoparticles interaction.